Self-perceived oral health assessment of institutionalized elderly of Viseu - Veiga, N. (2019)
Background: Self-perception of oral health is a multidimensional measure that, reflects the subjective experience of individuals about their physical and psychosocial well-being, determines the search for prevention and dental treatments.Objective: The assessment of the self-perception of oral health status of institutionalized elderly through the Geriatric Oral Health Assessment Index (GOHAI) and the verification of the association between the GOHAI and the various socio-demographic variables and oral health behaviors analyzed. Participants and methods: With this study we intended to conduct a cross-sectional observational epidemiological study with institutionalized elderly. Data were collected from a sample of 56 institutionalized elderly of the Mariana Seixas Foundation and the Viscondessa São Caetano Nursing Home in Viseu, Portugal. For this we used a questionnaire that allows to evaluate the self-perception of oral health, the Geriatric Oral Health Assessment Index (GOHAI). Results: It was found that the elderly generally favorably assessed their oral health, with 42.9% of the participants having a high self-perception of their oral health (values between 34-36); 28.6% have a moderate perception (values between 30-33) and the same percentage of individuals (28.6%) have a low perception (values below 30) of their oral health. The GOHAI scores obtained are associated with gender, educational level and oral health behaviors. Conclusion: Literacy can influence the level of self-perception of oral health. Therefore, the development of measures to assess oral health status is essential for the evolution of scientific knowledge based on geriatric dentistry in order to determine oral health promotion strategies among the institutionalized elderly.